2021
DOI: 10.3390/pharmaceutics13050635
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Properties of Concentrated Growth Factors (CGFs): The Role of Soluble Factors and Cellular Components

Abstract: Blood-derived concentrated growth factors (CGFs) represent a novel autologous biomaterial with promising applications in regenerative medicine. Angiogenesis is a key factor in tissue regeneration, but the role played by CGFs in vessel formation is not clear. The purpose of this study was to characterize the angiogenic properties of CGFs by evaluating the effects of its soluble factors and cellular components on the neovascularization in an in vitro model of angiogenesis. CGF clots were cultured for 14 days in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 81 publications
4
22
0
Order By: Relevance
“…In particular, the amount of VEGF in the CGF-conditioned medium after a 14-day incubation was even greater than the amount of VEGF extracted from the CGF. These results agree with our previous study showing that CGF-derived cells expressed and released angiogenic factors, including VEGF [22].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, the amount of VEGF in the CGF-conditioned medium after a 14-day incubation was even greater than the amount of VEGF extracted from the CGF. These results agree with our previous study showing that CGF-derived cells expressed and released angiogenic factors, including VEGF [22].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we demonstrated the ability of CGF to promote the osteogenic differentiation of stem cells [11]. Furthermore, we showed that CGF releases endothelial progenitor cells, which contribute to neo-angiogenesis and to the formation of endothelial tubular structures [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, matrix metalloproteinases, especially matrix metalloproteinases 1 and 2, mediate degradation of the capillary wall and the extracellular matrix components urokinase and integrins favouring ECs migration towards the extracellular matrix [37]. Angiopoietin-1 (Ang1) promotes the reorganization of the ECs in stable tubules with a central lumen, and platelet-derived growth factor (PDGF) action results in formation of a vascular network with the newly formed tubules [38,39].…”
Section: Angiogenesis and Pathological Implicationsmentioning
confidence: 99%